Thermostable Chicken Feather Degrading Enzymes from L-23 Isolate from Indonesia - ROSA SURYANTINI; REINE SUCI WULANDARI; RINA SRI KASIAMDARI (Microbiology Indonesia, 2007)
The thermostable chicken feather degrading protease enzymes used here was extracted and partially purified from thermophilic bacteria L-23 isolated from a coastal hot spring in North Sulawesi, Indonesia. The L-23 was grown in the selective medium containing 1% chicken feather powder at 70 °C and pH 7. The cell-free culture was precipitated with ammonium sulphate at 80% saturation, followed by heating at 65 °C for 1 h before applied onto Sephadex G-100. The molecular weight of the two enzymes identified were estimated as 47 and 64 kDa. The optimum pH of the mixed enzymes preparation was 7 while the optimum temperature was 65 °C. Zymogram analysis showed that one of the enzymes was still active after being heated at 100 °C for 20 min and was also resistant towards organic solvents and SDS. The activity was enhanced by addition of 1 mM FeCl3.